CONTRIBUTION OF VANGASENA IN THE FIELD OF PANCHAKARMA - Rajput, *Ravindrasingh; H, Yashaswini (AYUSHDHARA, 2017)
There are many references for Panchakarma in Brihat trayi and many Yogas for Shodhana therapy. Vangasena samhita is unique which covers all the subjects of Astangas with some specific Panchakarma procedures which are unique one. It contains many points explained in Brihat trayi along with some special things like Yogas, Matras. Yogas- mentioned some new Yogas for Shodhana (Aushadhi Kalpana) Matra -mentioned specific dosage of Snehapana and Dravya matra for Shodana based on Agni and Kostha. Speciality-some special Basti’s like Kshara basti and Vaitarana basti explained under the Amavata context which is most effective one. Highlights-For the first time mentioned Vardhamana matra of Snehapana with dosage and Vardhamana matra of Matra basti with dosage and duration. Many such unique concepts explained by Vangasena under Panchakarma. Most of the Yogas and procedure are not being in present day to day practice hence for the reason here an attempt made to highlight the important Yogas and concepts of Panchakarka explained by Vangasena and make implementation of concepts in practice for the maximum efficacy and beneficial.